Myopathy in the York Platelet Syndrome: An Underrecognized Complication. (12th August 2018) - Roman, Joy; Palmer, Michael I.; Palmer, Cheryl A.; Johnson, Nicholas E.; Butterfield, Russell J.
Abstract : York Platelet Syndrome (YPS) is a calcium channelopathy caused by gain of function in STIM1, a gene which acts as a calcium sensor. It is characterized by platelet abnormalities and muscle weakness. Medical literature emphasizes the hematologic aspects of the cases with few data of the neuromuscular and neuropathologic evaluation. We present a patient with YPS whose myopathy was the most prominent aspect. She presented around 2 years of age with proximal weakness and easy bruisability. YPS was diagnosed in the infant at 16 months of age at the National Institutes of Health. Muscle biopsy demonstrated a severe chronic myopathy. Rimmed vacuoles and tubular aggregates were noted. Although YPS is rare, the combination of a congenital myopathy with thrombocytopenia may facilitate the diagnosis and enable further insights into the disease.